More than enough : the ten keys to changing your financial destiny - Ramsey, Dave; Ramsey, Sharon (New York : Penguin Books, 2002)
Drawing from his years of work with thousands of families and corporate employees, Ramsey presents the ten keys that guarantee family and financial peace, including: values, goals, patience, discipline, and giving back to one's community. Using these essential steps anyone can create prosperity, live debt-free, and achieve marital bliss around the issue of finances. --from publisher description.
More than enough what? -- The missing link -- Victory through vision -- The "you" in "unity" is silent -- Hope: balm for the soul -- Accountability: how to get an A in conduct -- Intensity: feeling the fervor -- Good, better, best: work, discipline, diligence -- Patience is golden -- Looking for love in all the wrong places -- The great misunderstanding -- The more than enough road.
Originally published with a different subtitle by: New York : Viking, 1999.
Includes bibliographical references (pages 329-330).
Keywords: Finance, Personal; Finance, Personal -- Religious aspects -- Christianity; Finance, Personal; Finance, Personal -- Religious aspects -- Christianity; Nonfiction